2022
DOI: 10.3390/horticulturae8111075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Macronutrient Fertility on Mineral Uptake and Growth of Lactuca sativa ‘Salanova Green’ in a Hydroponic System

Abstract: Lactuca sativa (commonly referred to as lettuce) is one of the most popular grown hydroponic crops. While other fertilizer rate work has been conducted on lettuce, the impact of each element has not been evaluated independently or by determining adequate foliar tissue concentrations when all nutrients are plant-available. This study explores the impact that macronutrients have on the growth and yield of lettuce at different stages of the production cycle. Additionally, this study explores the adequate nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…1, Tables 2 and 3). A recommended sufficiency range of 4.38% to 5.79% N expands the N sufficiency ranges of 4.2% to 5.6% N (Bryson et al 2014) and 4.8% to 5.5% N (Veazie et al 2022). In addition, the deficiency value of 2.84% N was similar to the 2.65% N reported by Henry et al (2018), confirming that <2.84% N is inclusive of previously reported deficiency values.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1, Tables 2 and 3). A recommended sufficiency range of 4.38% to 5.79% N expands the N sufficiency ranges of 4.2% to 5.6% N (Bryson et al 2014) and 4.8% to 5.5% N (Veazie et al 2022). In addition, the deficiency value of 2.84% N was similar to the 2.65% N reported by Henry et al (2018), confirming that <2.84% N is inclusive of previously reported deficiency values.…”
Section: Resultsmentioning
confidence: 99%
“…High foliar N concentrations can lead to lower boron (B), copper (Cu), and potassium (K) foliar concentrations (Marschner 1995). Veazie et al (2022) reported a quadratic plateau regarding N foliar concentration of 5.41% for 8-week-old lettuce grown using an N fertility rate of 111.4 mg•L À1 N. The Weibull distribution curve establishes 6.89% N as the boundary between high and excessive concentrations and offers a target value for possible future refinement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silicon plays a very important role in the absorption of such ions by plant tissues (Pavlovic et al, 2021). According to the article, among the macronutrients, nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg) and calcium (Ca) are affected differently and not separately (Veazie et al, 2022). In addition, Si also plays an important role in plant uptake of certain trace elements such as boron (B) and manganese (Mn) (Pavlovic et al, 2021).…”
Section: Introductionmentioning
confidence: 99%